Preparation method of low-porosity and high-dielectric aramid paper
By using dimethylacetamide and inorganic nanoparticles in the preparation process of aramid paper, the existing aramid paper has been solved, and aramid paper with low porosity and high dielectric properties has been achieved.
Patent Information
- Application Number
- CN202411890521.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-04
AI Technical Summary
Due to the limited number of hydrogen bonds in the fiber network, existing aramid paper has weak interface bonding between fibers, loose paper structure, and porous structure affects paper strength and becomes a weak point of electric breakdown.
By adding dimethylacetamide and inorganic nanoparticles to the aramid stock solution, the PMIA/CaCl2/DMAc aramid stock solution is formed, and the fiber contact area is increased by using the swelling and dissolution characteristics of DMAc, and the inorganic nanoparticles are adsorbed on the fiber in situ through hydrogen bonding to fill the gaps on the paper surface.
The porosity of aramid paper is reduced, the overall performance of the paper is improved, the mechanical and insulation properties are enhanced, and the resistance to electric breakdown is improved.
Smart Images

Figure CN119553532A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aramid paper preparation, in particular to a method for preparing low-porosity and high-dielectric aramid paper. Background Art
[0002] In the prior art, aramid fiber (poly(m-phenylene isophthalamide)) is prepared by polycondensation of isophthaloyl chloride and m-phenylenediamine and then spinning. The prepared meta-aramid fiber has ultra-high specific strength, modulus, excellent heat resistance and insulation performance. Meta-aramid paper is a material made of aramid fiber (aramid fiber and aramid short fiber) through wet papermaking and hot pressing processes. Aramid paper has excellent high temperature resistance, insulation, chemical stability and flame retardancy.
[0003] In the existing aramid paper preparation technology, since the number of hydrogen bonds in the aramid fiber network is quite limited, the interface bonding between the fibers is weak, resulting in a loose overall structure of the paper. The porous structure will affect the strength of the paper and become a weak point for electrical breakdown. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing low-porosity, high-dielectric aramid paper, which solves the problems mentioned in the above background technology.
[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing low-porosity, high-dielectric aramid paper, comprising the following preparation steps:
[0006] Step 1, preparation of aramid stock solution: adding dimethylacetamide to a mixed solution of meta-aramid (PMIA) and calcium chloride, heating to 35-45°C, stirring and reacting for 3.5-4.5 hours to obtain a PMIA / CaCl2 / DMAc solution;
[0007] Step 2, preparation of inorganic nanoparticle suspension: pour 0.5-2g of treated inorganic nanoparticles into 25-40mL of PMIA / CaCl2 / DMAc solution, and stir the reaction at 35-45°C for 1.5-2h to obtain PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles;
[0008] Step 3, aramid stock solution coating: Use a wire rod to coat the PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles on the front and back sides of the aramid base paper, leave it for 15-25 minutes, and then place the coated base paper in a vacuum drying oven at 90-105°C for 45-65 minutes;
[0009] Step 4: Hot pressing of the coated base paper: The coated aramid paper is subjected to hot pressing treatment to obtain low porosity and high dielectric aramid paper.
[0010] Preferably, in step 1, the mass ratio of meta-aramid to calcium chloride is (4.5-6):2.
[0011] Preferably, in step 2, the inorganic nanoparticles are selected from one or a combination of two or more of nano-aluminum oxide, nano-calcium carbonate, nano-magnesium hydroxide, nano-zinc oxide, nano-silicon dioxide, nano-titanium dioxide, nano-silicon carbide, and nano-boron nitride.
[0012] Preferably, the method for preparing the low-porosity, high-dielectric aramid paper further comprises modifying the inorganic nanoparticles, and the specific modification steps are:
[0013] S1. pretreating the inorganic nanoparticles;
[0014] S2, pouring 0.6-1.5 g of the pretreated inorganic nanoparticles and 4-5.5 g of lithium hydroxide monohydrate into 200-250 mL of a mixed solvent, and stirring the mixture at room temperature for 20-24 h;
[0015] S3, performing heating evaporation and concentration treatment, then washing the product with ethanol for 2-4 times, and then drying it in a vacuum drying oven at 50-60°C and grinding it.
[0016] Preferably, the mixed solvent is prepared by mixing anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is (1-1.5):1.
[0017] Preferably, the specific pretreatment steps of the inorganic nanoparticles are:
[0018] S11, pouring the inorganic nanoparticles into N-methylpyrrolidone solution and ultrasonically treating for 25-35 minutes;
[0019] S12, add sodium p-styrene sulfonate and azobisisobutyronitrile, raise the temperature to 60-70°C, and stir to react for 20-24h;
[0020] S13. After the reaction is completed, pour into ether solution to precipitate the product, then centrifuge, wash the product with methanol and ethanol alternately for 3-5 times, then place in a vacuum drying oven at 55-65°C and dry for 35-50 minutes before grinding.
[0021] Preferably, when pretreating the inorganic nanoparticles, the weight proportions of each component added are: 0.5-1.5 parts of inorganic nanoparticles, 50-75 parts of N-methylpyrrolidone solution, 2-5 parts of sodium p-styrene sulfonate, 0.1-0.4 parts of azobisisobutyronitrile, and 90-110 parts of ether solution.
[0022] Preferably, the aramid paper weight of a single layer is 15-35 g / m 2 .
[0023] Beneficial Effects
[0024] The present invention provides a method for preparing low-porosity, high-dielectric aramid paper. Compared with the prior art, the method has the following beneficial effects:
[0025] (1) The method for preparing low-porosity, high-dielectric aramid paper is based on the principle that dimethylacetamide can swell and dissolve aramid fibers, thereby increasing the contact area between aramid fibers and reducing the porosity of the aramid paper surface. After the aramid fibers are partially dissolved, the PMIA polymer in the PMIA / CaCl2 / DMAc aramid stock solution can form a uniform film on the aramid paper surface, thereby improving the overall performance of the paper.
[0026] (2) In the method for preparing low-porosity, high-dielectric aramid paper, inorganic nanoparticles are in-situ adsorbed on aramid fibers in aramid stock solution through hydrogen bonding, and can fill the gaps on the surface of the base paper after coating. The in-situ assembly of the nanoparticles can enhance the mechanical and insulating properties of the aramid paper.
[0027] In summary, the swelling and dissolution characteristics of DMAc are utilized to increase the contact area between aramid fibers, thereby reducing the porosity of the aramid paper surface. Secondly, after the aramid fibers are partially dissolved, the PMIA polymer forms a uniform film on the surface of the aramid paper, further improving the overall performance of the paper. In addition, the inorganic nanoparticles are in situ adsorbed on the aramid fibers through hydrogen bonding, and after coating, they effectively fill the gaps on the surface of the base paper, enhancing the mechanical and insulating properties of the aramid paper; the present invention not only reduces the porosity of the aramid paper, but also improves its insulating properties, showing excellent results. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are SEM images of the aramid base paper of the present invention before and after being coated with the aramid stock solution. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In this technical solution, the weight of a single-layer aramid paper is 15-35g / m 2 ; The inorganic nanoparticles are nano-alumina.
[0031] Example 1
[0032] A method for preparing low-porosity, high-dielectric aramid paper comprises the following steps:
[0033] Step 1, preparation of aramid stock solution: adding dimethylacetamide to a mixed solution of meta-aramid and calcium chloride in a mass ratio of 4.5:2, heating to 35°C, stirring and reacting for 3.5h to obtain PMIA / CaCl2 / DMAc solution;
[0034] Step 2: Preparation of inorganic nanoparticle suspension: Pour 0.5 g of the treated nano-alumina into 25 mL of PMIA / CaCl2 / DMAc solution, and stir the reaction at 35°C for 1.5 h to obtain a PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles;
[0035] The specific processing steps of the inorganic nanoparticles are as follows: pour 0.5g of the inorganic nanoparticles into 50-75g of N-methylpyrrolidone solution, and ultrasonically treat for 25min; add 2g of sodium p-styrene sulfonate and 0.1g of azobisisobutyronitrile, heat to 600°C, and stir to react for 20h; after the reaction is completed, pour into 90g of ether solution to precipitate the product, and then centrifuge, wash the product with methanol and ethanol alternately 3 times, and then place it in a vacuum drying oven at 55°C to dry for 35min and grind; take 0.65g of the ground inorganic nanoparticles and 4g of lithium hydroxide monohydrate and pour them into 2000mL of a mixed solvent of anhydrous ethanol and deionized water with a volume ratio of 1:1, and stir to react for 20h at room temperature; perform heating evaporation concentration treatment, and then wash the product with ethanol 2-times, and then place it in a vacuum drying oven at 50°C to dry and grind;
[0036] Step 3, aramid stock solution coating: Use a wire rod to coat the PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles on the front and back sides of the aramid base paper, leave it for 15 minutes, and then place the coated base paper in a vacuum drying oven at 90°C for 45 minutes;
[0037] Step 4: Hot pressing of the coated base paper: The coated aramid paper is subjected to hot pressing treatment to obtain low porosity and high dielectric aramid paper.
[0038] Example 2
[0039] A method for preparing low-porosity, high-dielectric aramid paper comprises the following steps:
[0040] Step 1, preparation of aramid stock solution: adding dimethylacetamide to a mixed solution of meta-aramid and calcium chloride in a mass ratio of 5:2, heating to 40°C, stirring and reacting for 4 hours to obtain PMIA / CaCl2 / DMAc solution;
[0041] Step 2, preparation of inorganic nanoparticle suspension: Pour 1.2 g of the treated inorganic nanoparticles into 30 mL of PMIA / CaCl2 / DMAc solution, and stir the reaction at a temperature of 35-45°C for 1.8 h to obtain a PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles;
[0042] The specific processing steps of the inorganic nanoparticles are as follows: pour 1g of the inorganic nanoparticles into 65g of N-methylpyrrolidone solution, and ultrasonically treat for 30min; add 3.5g of sodium p-styrene sulfonate and 0.2g of azobisisobutyronitrile, heat to 65°C, and stir to react for 22h; after the reaction is completed, pour into 100g of ether solution to precipitate the product, and then centrifuge, wash the product with methanol and ethanol alternately 4 times, and then place it in a vacuum drying oven at 60°C to dry for 40min and grind; take 1.2g of the ground inorganic nanoparticles and 4.5g of lithium hydroxide monohydrate and pour them into 220mL of a mixed solvent of anhydrous ethanol and deionized water with a volume ratio of 1.2:1, and stir to react for 22h at room temperature; perform heating evaporation concentration treatment, and then wash the product with ethanol 3 times, and then place it in a vacuum drying oven at 55°C to dry and grind;
[0043] Step 3, aramid stock solution coating: Use a wire rod to coat the PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles on the front and back sides of the aramid base paper, leave it for 205 minutes, and then place the coated base paper in a vacuum drying oven at 100°C for 55 minutes;
[0044] Step 4: Hot pressing of the coated base paper: The coated aramid paper is subjected to hot pressing treatment to obtain low porosity and high dielectric aramid paper.
[0045] Example 3
[0046] A method for preparing low-porosity, high-dielectric aramid paper comprises the following steps:
[0047] Step 1, preparation of aramid stock solution: adding dimethylacetamide to a mixed solution of meta-aramid and calcium chloride in a mass ratio of 6:2, heating to 45°C, stirring and reacting for 4.5 hours to obtain PMIA / CaCl2 / DMAc solution;
[0048] Step 2: Preparation of inorganic nanoparticle suspension: Pour 2 g of treated inorganic nanoparticles into 40 mL of PMIA / CaCl2 / DMAc solution, and stir the reaction at 45°C for 2 h to obtain PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles;
[0049] The specific processing steps of the inorganic nanoparticles are as follows: pour 1.5g of the inorganic nanoparticles into 50-75g of N-methylpyrrolidone solution, and ultrasonically treat for 35min; add 5g of sodium p-styrene sulfonate and 0.4g of azobisisobutyronitrile, heat to 70°C, and stir to react for 24h; after the reaction is completed, pour into 90-110g of ether solution to precipitate the product, and then centrifuge, wash the product with methanol and ethanol alternately for 5 times, and then dry it in a vacuum drying oven at 65°C for 50min and grind it; take 0.6-1.5g of the ground inorganic nanoparticles and 5.5g of lithium hydroxide monohydrate and pour them into 250mL of a mixed solvent of anhydrous ethanol and deionized water with a volume ratio of 1.5:1, and stir to react for 20-24h at room temperature; perform heating evaporation concentration treatment, and then wash the product with ethanol 4 times, and then dry it in a vacuum drying oven at 60°C and grind it;
[0050] Step 3, aramid stock solution coating: Use a wire rod to coat the PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles on the front and back sides of the aramid base paper. After staying for 25 minutes, place the coated base paper in a vacuum drying oven at 105°C for 65 minutes;
[0051] Step 4: Hot pressing of the coated base paper: The coated aramid paper is subjected to hot pressing treatment to obtain low porosity and high dielectric aramid paper.
[0052] Comparative Example 1
[0053] Compared with Example 1, the difference is that no inorganic nanoparticles are added; the rest remains unchanged.
[0054] Comparative Example 2
[0055] Compared with Example 1, the difference is that dimethylacetamide is not added; the rest remains unchanged.
[0056] Tensile strength test: The test was conducted according to GB / T 12914-2008; the results are shown in Table 1.
[0057] Tear strength test: The test was conducted according to GB / T 455-2002; the results are shown in Table 1.
[0058] Electrical strength test: The test was conducted in accordance with GB / T1408.1-2006; the results are shown in Table 1.
[0059] Table 1
[0060]
[0061] like Figure 1As shown in the figure, due to the smooth surface of aramid chopped fibers, fewer chemically active groups, poor adhesion and wettability, there are only very few hydrogen bonds between the fibers, weak interfacial bonding force, and many pore structures will be produced between the loosely bonded fibers; after coating with aramid stock solution, the surface of the aramid base paper becomes dense, and there is no obvious exposure of aramid chopped fibers.
[0062] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing low-porosity, high-dielectric aramid paper, characterized in that: The method comprises the following preparation steps: Step 1, preparation of aramid stock solution: adding dimethylacetamide to a mixed solution of meta-aramid and calcium chloride, heating to 35-45°C, stirring and reacting for 3.5-4.5 hours to obtain a PMIA / CaCl2 / DMAc solution; Step 2, preparation of inorganic nanoparticle suspension: pour 0.5-2g of treated inorganic nanoparticles into 25-40mL of PMIA / CaCl2 / DMAc solution, and stir the reaction at 35-45°C for 1.5-2h to obtain PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles; Step 3, aramid stock solution coating: Use a wire rod to coat the PMIA / CaCl2 / DMAc aramid stock solution containing inorganic nanoparticles on the front and back sides of the aramid base paper, leave it for 15-25 minutes, and then place the coated base paper in a vacuum drying oven at 90-105°C for 45-65 minutes; Step 4: Hot pressing of the coated base paper: The coated aramid paper is subjected to hot pressing treatment to obtain low porosity and high dielectric aramid paper.
2. The method for preparing low-porosity, high-dielectric aramid paper according to claim 1, characterized in that: In the step 1, the mass ratio of meta-aramid to calcium chloride is (4.5-6):
2.
3. The method for preparing low-porosity, high-dielectric aramid paper according to claim 1, characterized in that: In the step 2, the inorganic nanoparticles are selected from one or a combination of two or more of nano-aluminum oxide, nano-calcium carbonate, nano-magnesium hydroxide, nano-zinc oxide, nano-silicon dioxide, nano-titanium dioxide, nano-silicon carbide, and nano-boron nitride.
4. The method for preparing low-porosity, high-dielectric aramid paper according to claim 1, characterized in that: The method for preparing the low-porosity, high-dielectric aramid paper further includes modifying the inorganic nanoparticles, and the specific modification steps are: S1. pretreating the inorganic nanoparticles; S2, pouring 0.6-1.5 g of the pretreated inorganic nanoparticles and 4-5.5 g of lithium hydroxide monohydrate into 200-250 mL of a mixed solvent, and stirring the mixture at room temperature for 20-24 h; S3, performing heating evaporation and concentration treatment, then washing the product with ethanol for 2-4 times, and then drying it in a vacuum drying oven at 50-60°C and grinding it.
5. The method for preparing low-porosity, high-dielectric aramid paper according to claim 4, characterized in that: The mixed solvent is prepared by mixing anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is (1-1.5):
1.
6. The method for preparing low-porosity, high-dielectric aramid paper according to claim 4, characterized in that: The specific pretreatment steps of the inorganic nanoparticles are: S11, pouring the inorganic nanoparticles into N-methylpyrrolidone solution and ultrasonically treating for 25-35 minutes; S12, add sodium p-styrene sulfonate and azobisisobutyronitrile, raise the temperature to 60-70°C, and stir to react for 20-24h; S13. After the reaction is completed, pour into ether solution to precipitate the product, then centrifuge, wash the product with methanol and ethanol alternately for 3-5 times, then place in a vacuum drying oven at 55-65°C and dry for 35-50 minutes before grinding.
7. The method for preparing low-porosity, high-dielectric aramid paper according to claim 6, characterized in that: When pretreating the inorganic nanoparticles, the weight proportions of each component added are: 0.5-1.5 parts of inorganic nanoparticles, 50-75 parts of N-methylpyrrolidone solution, 2-5 parts of sodium p-styrene sulfonate, 0.1-0.4 parts of azobisisobutyronitrile, and 90-110 parts of ether solution.
8. The method for preparing low-porosity, high-dielectric aramid paper according to claim 1, characterized in that: The aramid paper weight of a single layer is 15-35g / m 2 .